Technology Driven Mitigation of COVID-19 Infection Risk in Retinal Surgery, by means of 3D Visualization Systems - Pappas, George; Vidakis, Nectarios; Petousis, Markos (Journal of Ophthalmology and Research, 2020)
In cases in which the proximity of the medical personnel and the patient is necessary, such as in ophthalmology, both the medical personnel and the patient have high infection risk from each other’s respiratory system secretions, which can float in a range usually larger than the required proximity of such medical operations. In this work, the authors examine and evaluate the infection risk change between the ordinary retinal operation practice with microscope and the one with utilizing a 3D visualization system, by keeping the other surgery conditions untouched. It was found that the 3D visualization provides a significant reduction of the COVID-19 infection risk for the surgeon, his paramedics’ assistant, and the patient. Many reasons trigger ophthalmologists to use this new way of operating; The ergonomics for the surgeon, the excellent image quality, the better depth of view, the ability to reproduce large differences in bright and dark conditions to retain details and depends on the ability of the human pupil to fluctuate in size, the ability to change lighting conditions, the teaching potential and the ease to adapt.